Correlates of turnover intention among nursing staff in the COVID-19 pandemic: a systematic review - Katharina Herta Tolksdorf; Ulla Tischler; Katherina Heinrichs (BMC Nursing, 2022)
Abstract Background During the COVID-19 pandemic, shortage of nursing staff became even more evident. Nurses experienced great strain, putting them at risk to leave their jobs. Individual and organizational factors were known to be associated with nurses’ turnover intention before the pandemic. The knowledge of factors associated with turnover intention during the pandemic could help to foster nurses’ retention. Therefore, this review aims to identify factors associated with nurses’ turnover intention during the COVID-19 pandemic. Methods After a systematic search of six databases, the resulting records were screened in a two-step process based on pre-defined inclusion and exclusion criteria. The included quantitative studies were synthesized qualitatively due to their methodological heterogeneity. Results A total of 19 articles were included in the analysis. Individual factors such as health factors or psychological symptoms and demographic characteristics were associated with nurses’ turnover intention. Organizational factors associated with turnover intention were e.g., caring for COVID-19 patients, low job control or high job demands, and moral distress. Resilience and supporting leadership could mitigate adverse associations with turnover intention. Conclusions The results help to identify high-risk groups according to individual factors and to develop possible interventions, such as trainings for nurses and their superiors, addressing individual and organizational factors. Future research should focus on longitudinal designs applying carefully defined concepts of turnover intention.